Research progress on the effects and mechanisms of magnetic field on neurodegenerative diseases - Ding, Shuxian; Li, Jinhua; Fang, Yanwen; Zhuo, Xingjie; Gu, Lili; Zhang, Xinyue; Yang, Yuanxiao; Wei, Min; Liao, Zhongcai; Li, Qin (Progress in biophysics and molecular biology, 2024)
With the progress of modern science and technology, magnetic therapy technology develops rapidly, and many types of magnetic therapy methods continue to emerge, making magnetic therapy one of the main techniques of physiotherapy. With the continuous development of magnetic field research and clinical applications, magnetic therapy, as a non-invasive brain stimulation therapy technology, has attracted much attention due to its potential in the treatment of motor dysfunction, cognitive impairment and speech disorders in patients with neurodegenerative diseases. However, the role of magnetic fields in the prognosis and treatment of neurodegenerative diseases and their mechanisms remain largely unexplored. In this paper, the therapeutic effect and neuroprotective mechanism of the magnetic field on neurodegenerative diseases are reviewed, and the new magnetic therapy techniques are also summarized. Although the neuroprotective mechanism of magnetic field cannot be fully elaborated, it is helpful to promote the application of magnetic field in neurodegenerative diseases and provide a new theoretical basis for the related magnetic field research in the later period. •Summarize the therapeutic effect of magnetic field on neurodegenerative diseases and new magnetic therapy technology.•A variety of potential mechanisms play a neuroprotective role of magnetic field.•Magnetic therapy technology have great potential in the treatment of neurodegenerative diseases.